Accessing Choice: A Mixed-Methods Examination of How Latino Parents Engage in the Educational Marketplace. (November 2016) - Mavrogordato, Madeline; Stein, Marc
School choice has become a cornerstone of education reform plans across the nation especially in urban settings where immigrant populations often settle. Latino enrollment in charter schools has increased accordingly. Yet, little is known about how Latino parents, who arguably face significant linguistic, cultural, and economic barriers, engage in the choice process. This study examines what motivates Latino and non-Latino parents to consider a charter school and what informs their decision to enroll their children. By comparing these groups, we seek to better understand how parents, particularly those who face layers of disadvantage like Latinos, interact with the educational marketplace.